Participatory, demonstration and evaluation of different fish recipe to the local community from Tekeze Reservoir; Wag-Lasta, Ethiopia - Bekele, Alachew Adino (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Fish and fishery products are well known for their high nutritional value and quality; specifically, they are relatively low in fat, saturated fat, omega 3, and cholesterol, yet they are high in polyunsaturated fatty acids, protein, and minerals. The objective of the study is participatory sensory evaluation of fish products (meat) in different food items for the local community. The study was carried out in three selected districts (Abergele, Zequala, and Sehala) in the Waghemira zone of the Amhara region of northern Ethiopia. The fish recipes were fish stew (asa wote), fish duel (asa dulet), fish fry (asa tibs), fish goulash (asa gulesh), fish hamburger (asa hamburger), fish palpetii (asa palpetii), and dried fish (asa quanta). Sehala district, fish fry, fish goulash, fish palpatii, and dried fish scored the highest. In the Abergele fish duel, the fish stew score was the highest. The highest scores for fish recipe tenderness and texture were found in Abergele district, where fish stew was the most popular. In conclusion, the participatory demonstration and evaluation of fish recipes in the Waghimra Zone showed promising results in terms of community engagement, overall acceptance, and the potential for developing local fishery resources. Future studies and continued monitoring are recommended to further explore and scale up dried fish, fish fry, fish goulash, and fish duel.